Spectral Analysis based on Stimulated Brillouin Scattering Effect - GUO Li-jun; TAN Zhong-wei (Guangtongxin yanjiu, 2023)
Optical filters are widely used in many applications, including optical communication, spectroscopy, electronics and optical sensors. The Microwave Photonic Filter (MPF) based on Stimulated Brillouin Scattering (SBS) effect not only has the advantages of low threshold and high gain, but also has the characteristics of reconfiguration and tunability. In this paper, we apply MPF to spectral analysis. Using the tunability of the filter, the spectrum of the whole signal can be measured. And the different frequency components of the signal can be extracted by time-sharing. By setting the center frequency of the swept laser in the pump branch of the filter, the output power of the filter is measured by the optical spectrum analyzer after SBS effect generating by the pump excitation, so as to analyze the spectrum of the signal light. The results show that with the increase of pump power, the filter gain and Out of Band Rejection Ratio (OOBR) first increase and then decrease. The inflection point is about 5 dBm and the dynamic range of the filter is from -35 to -20 dBm.